Isokinetic profile of wrist and forearm strength in elite female junior tennis players - Ellenbecker, T. S.; Roetert, E. P.; Riewald, S. (British Journal of Sports Medicine, 2006)
Background: In tennis, injuries to the elbow and wrist occur secondary to the repetitive nature of play and are seen at increasingly young ages. Isokinetic testing can be used to determine muscular strength levels, but dominant/non-dominant and agonist/antagonist relations are needed for meaningful interpretation of the results.